2002
DOI: 10.1042/cs103s399s
|View full text |Cite
|
Sign up to set email alerts
|

Arteriojugular endothelin-1 gradients in aneurysmal subarachnoid haemorrhage

Abstract: Plasma endothelin (ET) is elevated in patients with vasospasm following subarachnoid haemorrhage (SAH). However, systemic levels provide no indication regarding local production in the brain, and late elevation may be a consequence rather than a cause of vasospasm. We measured arteriojugular (AJ) gradients of ET-1 in 17 patients over the first week after SAH, and related these to the subsequent development of vasospasm. Daily, paired arterial and jugular bulb blood samples were obtained up to seven days post S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These findings might possibly be explained epiphenomenally due to the ET-1 conversion rate in the endothelial basilar arterial layer or due to ET-1 release from the CSF into the cerebral circulation. This hypothesis might also be supported by Menon et al who found high arteriojugularvenous ET-1 gradients in patients suffering from SAH-induced CVS [15].…”
Section: Local Levels Of No Metabolitesmentioning
confidence: 54%
See 2 more Smart Citations
“…These findings might possibly be explained epiphenomenally due to the ET-1 conversion rate in the endothelial basilar arterial layer or due to ET-1 release from the CSF into the cerebral circulation. This hypothesis might also be supported by Menon et al who found high arteriojugularvenous ET-1 gradients in patients suffering from SAH-induced CVS [15].…”
Section: Local Levels Of No Metabolitesmentioning
confidence: 54%
“…[7,8] The controversy is still ongoing although preclinical and clinical trials using intracarotid infusion of NO gas solution, [9] intracarotid or intrathecal administration of NO donors [10][11][12] and ET-1 receptor inhibitors have claimed clinical success. [13,14] However, better understanding of aSAH pathophysiology, discovery of new aSAHrelated events like cortical spreading ischemia [15] and, probably most importantly, the failure of Clazosentan, a selective ET-1 A receptor inhibitor, in Phase II clinical study [2] to improve the outcome despite prevention of vasospasm all lead to a paradigm shift with the focus on the possibility that a stroke after aSAH may be evoked by another nonvasospasm-related mechanism(s). Growing body of evidence suggests that these pathomechanisms are a result of the presence of an arterial blood clot in the subarachnoid space, increased ET-1 in CSF, and decreased availability of NO in cerebral arteries.…”
Section: Interaction Of Et-1 and Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Such an observation is in concordance with current knowledge about endothelin-1 concentrations rising in the first few days after rupture. (28,49,50) At the moment of awakening from general anesthesia, a lower pCO 2 in the jugular vein was found in the group of patients operated on after aneurismal rupture compared to the group operated on for a nonruptured cerebral aneurysm. A similar result was observed if the group of patients with supposed cerebral vasospasm and the group without it were compared, yet only with a borderline statistical significance.…”
Section: Discussionmentioning
confidence: 97%
“…A previously described method [26] for directly measuring mediator synthesis and release in the cerebrovascular bed was used to quantify the arteriovenous gradient of ET-1 and its precursor Big ET-1 across the brain. The venous samples used to make these calculations were obtained from jugular bulb catheters used for brain oximetry; when correctly positioned, these exclusively sample blood drained from the cerebrovascular bed.…”
Section: Introductionmentioning
confidence: 99%